STRATEGI PENGEMBANGAN USAHA BUDIDAYA RUMPUT LAUT DI KABUPATEN SERAM BAGIAN BARAT PROVINSI MALUKU - Yanti Rosmala; Andi Asni; Syahrul Djafar (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2020)
This study aims to determine the high feasibility of seaweed farming in Seram Regency, West Part of Maluku Province and to develop an appropriate development strategy in seaweed cultivation in Seram District, West Maluku Province. The analytical method used in this study is the analysis of seaweed farming and SWOT analysis. The main factors that influence the development of seaweed cultivation in Wael Hamlet (Piru Village) and Allang Asaude Village are: 1) The quality of the waters that are still suitable for seaweed cultivation activities, 2) The potential of Offshore Waters is still large enough for development seaweed cultivation business, 3) The method of seaweed cultivation is quite simple, 4) Seaweed cultivation can be done on a small business scale, 5) The high interest of the community to develop seaweed cultivation business, 6) The market demand is quite high for seaweed commodities, 7) Government attention to fisheries management is quite large. By using SWOT analysis in formulating strategies for developing seaweed cultivation business in Wael Hamlet (Piru Village) and Allang Asaude Village, alternative strategic priorities are: 1) Spatial/zoning arrangement of coastal and marine areas with a weight of 0.84 and 2) Increased cultivation bintek (seed selection, maintenance, post-harvest and business management weights 0.56.